Child Tobacco Smoke Exposure: Interventions for Busy Physicians - Kevin Nelson; Kasinda Goodwin; Rachel State; Wendy Hobson-Rohrer (Association of American Medical Colleges, 2016)
Abstract Introduction Smoking and tobacco smoke exposure (TSE) leads to 480,000 deaths and over $289 billion in medical costs and lost productivity annually. Among U.S. children, 44% are affected by TSE. TSE increases the frequency of low birth weight, sudden infant death syndrome, child ear infections, bronchiolitis, asthma, atherosclerosis, and neurobehavioral problems in children. Although parent motivation to quit smoking increases in healthcare settings, TSE interventions are delivered infrequently. Many pediatric residency programs provide no formal training in parent TSE interventions. With few exceptions, education resources for parent TSE interventions often omit participant-reported TSE intervention practice patterns, participant barriers, and physician workflow and are not peer reviewed. Methods This module is designed to address these gaps and improve delivery of TSE interventions to parents who smoke. The training module uses small-group training sessions and the evidence-based Ask, Advise, Refer strategy for smoking cessation to: provide training in evidence-based screening for child TSE, provide parent smoking cessation advice, and use referrals to evidence-based smoking cessation resources. Results The training module was implemented with 42 pediatricians at 10 pediatric practices in Utah. The included provider assessment tool was completed by 60% of participants prior to receiving the training module. Posttraining responses to the provider assessment tool indicated that implementation of the training module met the learning objectives for pediatrician knowledge and practice related to TSE and TSE interventions. Discussion Following the training module, 47% of physicians reported a high level of interest in maintenance of certification for TSE interventions. Our results suggest that implementation of the training module may help improve TSE intervention practices that support parent smoking cessation. Posttraining improvements in participant-reported practice patterns suggest that this training module has significant potential for changing provider practices.